Residents' Awareness of Forestry Knowledge and Practices for Flood Mitigation (A Case in South West Nigeria) - Adebayo Samson Adeoye; Olawale Julius Aluko; Oluwole Olalekan Oke (Buletin Penelitian Sosial Ekonomi Pertanian Fakultas Pertanian Universitas Haluoleo, 2025)
The combination of environmental degradation and inadequate engineering solutions has exacerbated flooding in Nigeria. Consequently, the study examined residents' awareness of forestry knowledge and practices. A 4-stage random sampling procedure was used, resulting in 250 participants selected via systematic sampling. Data were gathered through a structured questionnaire on residents' demographic characteristics, awareness of environmental practices, and utilization of forestry land-use practices. The analysis of data involved frequencies, percentages, mean values, rankings, and inferential statistics using the Chi-square test. The results showed that 68.0% of respondents were female, with a significant proportion (78.0%) aged 21-50 years. Additionally, 74.0% were married, 40.0% were civil servants, and 22.0% were involved in trading. The residents' knowledge revealed that the prohibition on disposing of refuse into drainage and rivers had a mean score of 1.6 and ranked 1st, while the government's advisories on relocation from flood-prone areas had a mean of 1.1, ranking 2nd in awareness. Chi-square analysis showed significant relationships between tree planting and flood experiences (χ² = 8.18, p = 4×10^-3) and between tree conservation and marital status (χ² = 10.61, p = 0.01). Furthermore, there was a significant association between other demographics, such as marital status (χ²=7.99, p = 0.05) and years of residence (χ²=16.03, p = 3˟10ˉ³), and forestry land use practices (FLUP). Key findings emphasized the critical role of tree planting, conservation, and environmental education in enhancing ecosystem resilience and mitigating climate-related disasters, such as floods, in southwest Nigeria.